Analisis Determinan Tingkat Literasi Keuangan Pedagang pada Pasar Tradisional di Kota Denpasar - Bonita, Ayu Putu Arantza; Setiawina, Nyoman Djinar (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 7, No. 2, Februari 2018 (pp. 212 - 380), 2018)
Financial literacy has become an important aspect for micro-small entrepreneurs to have good corporate performance, enabling micro-small businesses to grow. This study aims to determine the level of financial literacy traders in traditional markets in Denpasar and the influence of simultaneous and partial between the variables of education level, length of business and gender to the level of financial literacy traders in traditional markets in Denpasar. The population of this research is all traders in traditional markets in Denpasar in 2017 (sample saturated), with the number of samples were 99 respondents. The results showed that the majority of traders in traditional markets in Denpasar have the level of financial literacy in the category of being. Based on the results of data analysis found that simultaneously, all the independence variables which are, the variable level of education, length of business, and gender have a significant influence on the level of financial literacy traders in traditional markets in Denpasar. Partially, all the independence variables, except gender have positive and significant influence to the level of financial literacy of traders in traditional market in Denpasar.